(??????? ???? ??? ? ???? ?? (????? ????? ?????? ????? ??????? ?? ???? ????? ????? ????????? - Rahman Hakim; Nahdliyyatul ‘Azimah; Khoirin Nikmah (Universitas Islam Negeri Mataram, 2020)
Google meet and whatsapp are two technologies that are used byteachers as an alternative media for distance learning for Amanatul UmmahIslamic Boarding School students who want to continue their studies inthe Middle East. This study is classified as a descriptive-qualitative. Thedata collection was taken from questionnaires, interviews (unstructured),observation, and documentation. The primary data source is the AmanatulUmmah Islamic boarding school students who attended intensive Arabictutoring. The secondary data are taken from questionnaires, documentation,and literature study. The results showed that the use of the google meetand whatsapp applications was quite effective in delivering Arabic learningmaterials to students. That is supported by the results of the questionnairewhich shows that respondents are able to follow and understand onlinelearning using these two applications.